PENDEKATAN SHUHBAH DALAM BIMBINGAN KESEHATAN MENTAL UNTUK PARA SANTRI DI PONDOK PESANTREN SYAFIâIYAH CISAMBENG MAJALENGKA - supriadi, yedi (Oasis : Jurnal Ilmiah Kajian Islam, 2016)
Abstract, Mental health problems lately discussed actually by academics, politicians and psychiatrists. Even the president Joko Widodo also wants the mental of the civil in this country must be revolutioned because of mental Indonesian nation has degraded. It was characterized by the many cases of abuse and violence as children (sexual abuse of children), rape, murder, corruption, drug trafficking, terrorism acts and other criminal acts which turned mostly done by teenagers. Deviant behavior that occurs because it is caused by many factors, both internally and externally. Internal factors derived from yourself while external factors coming from outside, especially influenced of environmental factors, a culture that is less educated, less public role and influence of advances in information technology which presents many negative impressions. This is left unchecked will jeopardize the future of the next generations adolescence if not addressed. Problems in adolescent mental health disorders today increasingly reflect the concerns of parents, teachers and the community.The goal of the research are to describe the development of the mental health for young students at the boarding school in the islamic school of Syafiiyyah in Cisambeng city of Palasah-Majalengka regency. Development of mental health in question is with the planting of character and morals and a healthy mental approach to the students through some methode is called âshuhbahâ (friendship) for the purpose of mental development can be achieved easily, accurately, effectively and efficiently. The method of the research are using descriptive method with collecting some information, by techniques gained through observation, interviews, questionnaires and documentation study. Data retrieval is derived from respondents who are seen mental health problems with a purposive sampling technique that aims to find out what the problem occurs in teenagers these students then how after he followed the guidance of mental health at boarding Syafiiyyah Cisambeng approach by âshuhbahâ (friendship). Islamic conseling emphasizes spiritual solutions based on love and fear of Allah and the duty of fulfil our responsibility as the servants of Allah on this earthâThe results of the research illustrate that the application of mental health counseling with shuhbah (friendship) perceived benefit to the students who participated in mental health counseling because after being interviewed and completed questionnaires the students who have experienced problems of mental disorders (misconduct) after obtaining calculated the mean category average high.Based on the recognition of the students, they are feel much better after attending mental health training activities in Pondok Pesantren Syafiiyyah Cisambeng guided by Mas Nawawi (Ustd.Muhamad Nawawi Fathulloh, M.Pd.I). Thus the results of this study presented a picture of the actual conditions in the field as the information and report the study authors.Â Keywords: Model Guidance, Mental Health, and Pupils